Implikasi Penggunaan Media Sosial Dikalangan Remaja Pada Era Digital Perspektif Pendidikan Islam - Munawarsyah, Muzawir; Ratnasari, Dwi; Hafiun, Muhammad; Aziz, Abdullah (PAKAR Pendidikan, 2025)
The use of social media is often a threat to the character and behavior of adolescents in the current era of disruption. This study examines the impact of social media on adolescents in the digital era from the perspective of Islamic education. Through a qualitative phenomenological approach, this research involved six students of the Faculty of Da'wah and Communication of UIN Sunan Kalijaga Yogyakarta who have direct contact with social media, through the stages of interviews, observation, and documentation. The results of the study show that social media has positive impacts, such as facilitating access to information, building personal branding, and increasing insight, including in Islamic values. However, it also brings negative impacts, such as addiction, spreading false information, cyberbullying, and the FoMO (Fear of Missing Out) phenomenon. In addition, social media platform algorithms often control news information or content to its users that can affect the understanding of users' moral and religious values, so digital literacy and wisdom in filtering social media content are needed. Social media literacy in the perspective of Islamic education acts as a moral filter to help adolescents use social media wisely. So that through it can minimize the negative impact and shape the character of the younger generation in accordance with Islamic values.